The neurophysiology of human touch and eye gaze and its effects on therapeutic relationships and healing: a scoping review protocol. (April 2016) - Kerr, Fiona; Wiechula, Rick; Feo, Rebecca; Schultz, Tim; Kitson, Alison
Abstract : Review question/objective: The objective of this scoping review is to examine and map the range of neurophysiological impacts of human touch and eye gaze, and better understand their possible links to the therapeutic relationship and the process of healing. The specific question is "what neurophysiological impacts of human touch and eye gaze have been reported in relation to therapeutic relationships and healing?"